Reconceptualizing Due Process in Juvenile Justice: Contributions from Law and Social Science - Cross, Tricia (2006)
This article challenges the accepted wisdom, at least since the Supreme Court's decision in Gault, that procedures in juvenile delinquency court should mimic the adult criminal process. The legal basis for this challenge is Gault itself, as well as the other Supreme Court cases that triggered the juvenile justice revolution of the past decades, for all of these cases relied on the due process clause, not the provisions of the Constitution that form the foundation for adult criminal procedure. That means that the central goal in juvenile justice is fundamental fairness, which does not have to be congruent with the adversarial tradition of adult criminal court. Instead, as the Court's administrative procedure cases illustrate, fundamental fairness theory aims at constructing the procedural framework that best promotes fairness, accuracy and efficiency in the setting in question. Social science, and in particular procedural justice research, can play an important role in fashioning this framework, because it can empirically examine various procedural mechanisms, in various settings, with these objectives in mind. To date, procedural justice research suggests that the procedures associated with the adult criminal process are not optimal even in that setting, much less in a regime focused on rehabilitating or punishing children. We propose a performance-based management system for implementing these legal and scientific insights in the juvenile justice context